Design of Educational Playing Cards Featuring Biblical Characters as a Visual Learning Tool for Children - Chandra, Lidya Irawaty; Purba, Christin Agustina; Triztika, Rizka Alya (Journal Research of Social Science, Economics, and Management, 2026)
Religious education plays a crucial role in shaping children’s character and moral development from an early age, particularly through stories of Biblical figures that convey values such as obedience, love, courage, honesty, and faith in God. However, children’s reading interest remains relatively low, while most religious learning media are still presented in text-based formats that are less engaging. This creates challenges in delivering these values effectively. This study aims to design an interactive and engaging educational card game based on Biblical stories for children aged 5–10 years using the Design Thinking method. The process includes the stages of empathize, define, ideate, prototype, and test. The result of this study is an educational card game design that is expected to enhance children’s learning interest and facilitate their understanding of the values conveyed in Biblical stories. These findings imply that game-based visual learning media can serve as an effective alternative to text-based methods in children’s religious education.